MENELADANI MODEL KEPEMIMPINAN KRISTUS SEBAGAI MODEL KEPEMIMPINAN KRISTEN PADA ERA POST-MODERN: TINJAUAN 1 TIMOTIUS 3:1-7 - Wasti Potto Palullungan; Melyana Mangin Sosang, Wandayani Sirenden, Yeremia Patodingan, Yosia Oktovianri (CV. ADIBA AISHA AMIRA, 2023)
This research aims to comprehend and apply a leadership model inspired by Christ as an example for Christian leaders in the post-modern era. Christ-centered leadership, based on 1 Timothy 3:1-7, will be deeply analyzed and discussed to explore its relevance within the complex and diverse context of post-modern society. The research methodology encompasses the analysis of the Bible text in 1 Timothy 3:1-7 and a review of literature on Christian leadership. Data will be collected, analyzed, and translated into leadership principles applicable to everyday church and community life. The expected outcomes of this research are to provide a deeper understanding of how the Christ-centered leadership model can be integrated into the post- modern context. Additionally, this study can offer practical guidance for Christian leaders who wish to develop and implement Christ-centered leadership principles in their work. This research has the potential to make a significant contribution to our understanding of Christian leadership in the post-modern era, characterized by complexity, pluralism, and diverse moral challenges. By recognizing and emulating the Christ-centered leadership model, Christian leaders can become positive agents of change in this continually evolving and transforming society.